Evaluating an Enterprise-Wide Initiative to enhance healthcare coordination for rural women Veterans using the RE-AIM framework - Relyea, Mark R.; Kinney, Rebecca L.; DeRycke, Eric C.; Haskell, Sally; Mattocks, Kristin M.; Bastian, Lori A. (Frontiers in Health Services, 2024)
Introduction The Veterans Health Administration (VA) Office of Rural Health (ORH) and Office of Women's Health Services (OWH) in FY21 launched a three-year Enterprise-Wide Initiative (EWI) to expand access to preventive care for rural, women Veterans. Through this program, women's health care coordinators (WHCC) were funded to coordinate mammography, cervical cancer screening and maternity care for women Veterans at selected VA facilities. We conducted a mixed-methods evaluation using the RE-AIM framework to assess the program implementation. Materials and methods We collected quantitative data from the 14 program facilities on reach (i.e., Veterans served by the program), effectiveness (e.g., cancer screening compliance, communication), adoption, and maintenance of women's health care coordinators (WHCC) in FY2022. Implementation of the program was examined through semi-structured interviews with the facility WHCC funding initiator (e.g., the point of contact at facility who initiated the request for WHCC funding), WHCCs, and providers. Results Reach. The number of women Veterans and rural women Veterans served by the WHCC program grew (by 50% and 117% respectively). The program demonstrated effectiveness as screening rates increased for cervical and breast cancer screening (+0.9% and +.01%, respectively). Also, maternity care coordination phone encounters with Veterans grew 36%. Adoption: All facilities implemented care coordinators by quarter two of FY22. Implementation. Qualitative findings revealed facilitators and barriers to successful program implementation and care coordination. Maintenance: The EWI facilitated the recruitment and retention of WHCCs at respective VA facilities over time. Implications In rural areas, WHCCs can play a critical role in increasing Reach and effectiveness. The EWI demonstrated to be a successful care coordination model that can be feasibly Adopted, Implemented, and Maintained at rural VA facilities.